Increasing Plant Growth and Yield of Tomatoes (Solanum lycopersicum L.) by Providing Chicken Manure and Hormonics - Agusalim Masulili; Sri Rahayu; Sutikarini Sutikarini (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
Tomato cultivation in alluvial land requires treatments to increase productivity. The research aimed to determine the effect of interaction between chicken manure and hormonal fertilizer application on the growth and yield of tomato plants in alluvial soil. This research was conducted at the greenhouse of the Faculty of Agriculture, Science, and Technology, Panca Bhakti University from April to July 2023. A Completely Randomized Design (CRD) with a factorial pattern was employed. The treatments consisted of 2 factors. The first factor was chicken manure with 3 levels: a1= 20 g/polybag, a2= 40 g/polybag, a3= 60 g/polybag. The second factor was hormonal fertilizer with 3 levels: h1= 2 ml/l, h2= 3 ml/l, h3= 4 ml/l. The results showed that there was no interaction effect between the application of chicken manure and hormonal fertilizer on all observed variables, as well as the application of chicken manure alone. The application of hormonal fertilizer significantly affected all observed variables including plant height, number of branches, number of fruits, and fruit weight. The treatment level h2 (3 ml/l) yielded the highest result in plant height at 113.26 cm. The highest number of branches, number of fruits, and fruit weight were observed at the h3 level (4 ml/l) with values of 3.39 branches, 2.57 fruits, and a fruit weight of 86.10 grams, respectively. The treatment level h1 (2 ml/l) yielded the lowest result. Keywords: Alluvial Soil, Horticultural Commoditie, Organic Fertilizer.